Popular protest in East Germany, 1945-1989 - Dale, Gareth 1966- (Routledge advances in European politics, 2005)
Mass movements in the GDR's early years -- The June 1953 uprising -- Labour heritage and collective action, 1945-53 -- Infra-political resistance and social movements, 1954-88 -- Techniques of domination, arts of resistance -- Helsinki and Bohemia: emigration and youth rebellion -- 'Politics in the bell jar': socio-ethical movements in the 1980s -- The formation of political opposition -- The revolution of 1989 -- The summer crisis -- The autumn uprising -- Intellectuals and workers